Perumusan Strategi Pemberdayaan Petani Kakao Berdasarkan Persepsi Petani Terhadap Usaha Tani Kakao Di Desa Metun Sajau Kecamatan Tanjung Palas Timur - Muhammad Syafie; Dika Supyandi (Journal of Community Service and Engagement, 2026)
This activity aims to analyze the empowerment process of cocoa farmers, identify farmers’ perceptions toward cocoa farming, and formulate perception-based empowerment strategies in Metun Sajau Village. The activities were conducted using a quantitative survey approach supported by structured questionnaires with a Likert scale and semi-structured interviews to obtain both measurable and contextual data. The findings indicate that empowerment activities have been implemented through training, assistance, and institutional support; however, their effectiveness remains limited due to uneven distribution and lack of sustainability. Farmers generally show positive perceptions in technical aspects such as knowledge and motivation, but relatively low perceptions in economic aspects, particularly profitability. These perceptions significantly influence participation levels and adoption of innovations in cocoa farming practices. Based on these findings, empowerment strategies were formulated, including participatory training, continuous assistance, institutional strengthening, and market access development. These strategies are expected to enhance farmers’ capacity, independence, and productivity. Therefore, integrating farmers’ perceptions into empowerment activities is essential to ensure more adaptive, effective, and sustainable agricultural development outcomes.